Neutron radiography to study the water ingress via the interlayer of 3D printed cementitious materials for continuous layering. (20th October 2020) - Van Der Putten, J.; Azima, M.; Van den Heede, P.; Van Mullem, T.; Snoeck, D.; Carminati, C.; Hovind, J.; Trtik, P.; De Schutter, G.; Van Tittelboom, K.
Highlights: Continuous layering results in no preferential water ingress at the interfaces. An increased printing speed shows preferential water ingress through the sample sides. 3D printed specimens with SAPs have an increased water uptake ability and speed. By increasing the layer amount, the upper layer has the highest water uptake capacity. Abstract: 3D printing of cementitious materials is a developing technology in which structural elements are built via a layer-by-layer process. Among the many advantages of this technique, it is expected to lead to more sustainable structures due to a reduced waste generation and more efficient structural design, placing materials only where needed. However, the end result of this technique is a layered and anisotropic element, having a structural performance which is highly dependent on the quality of the interlayers. Also, the lack of moulding will induce more shrinkage resulting in an increased risk for crack formation. Both phenomena will not only endanger the structural behaviour of the printed specimen, also the durability will be affected in a negative way as cracks create preferential ingress paths for aggressive substances. Within the scope of this research, the transport of water through a printed element with short interlayer time gap (±15 s) is investigated, taking into account different printing speeds and different water ingress directions. To counteract shrinkage, the addition of superabsorbent polymers to the matrix is also investigated. The water transport was visualised by means of neutron radiography measurements and evaluated through quantitative and qualitative analysis of the obtained radiographs. In this study, upon continuous layering of the printed specimens, qualitative observations revealed no preferential water ingress through the interlayer when introducing water from the front surface. In all cases, increasing the printing speed decreases the water uptake ability. The addition of superabsorbent polymers has the opposite effect and increases the water uptake and uptake speed in systems with additional water to compensate for the loss in workability and showing the same effective water-to-cement ratio.